First Love in the Egodocuments of Girls in Interwar Poland. A Case Study of Texts by Irena Kwiatkowska and Sonia Caplan - Wilk, Marcin (Acta Poloniae Historica, 2025)
The article puts forward a comparative analysis of two egodocumentary accounts written by girls who grew up in interwar Poland. The study draws on selected educational brochures and psychological guides that defined the emotional norms for girls and young women. How did the authors talk about their “first love”? The research tools developed by historians of emotions, as well as the perspective of girlhood studies, enable us not only to explore the complex nature of this experience, which is embedded in various cultural and social discourses, but also to highlight its emancipatory aspects.